Model Bahan Ajar Bahasa Inggris Untuk SD Berbasis Pendekatan Kontekstual - Herlina Usman; Nidya Chandra Muji Utami; Otto Fajarianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
To develop a model of English language teaching materials based on a contextual approach. English learning in elementary school is the mastery and increase in the number and enrichment of vocabulary to support the mastery of the four English language skills, namely speaking, listening, reading and writing. This study uses mixed methods, research and development of teaching materials in research, adapted from the models of Borg and Gall and models of Dick, Carey and Carey. The four stages in this research are (1) the stage of research and information gathering, (2) the stage of draft development, (3) the stage of testing and product revision, (4) the stage of finalization and dissemination. The results of the research and development were obtained in the fifth grade English language teaching material model. Through a series of stages of developing instructional materials, a product of English language teaching materials for the fifth-grade elementary school was obtained based on a contextual approach that fulfills the characteristics of good teaching materials that can be used by fifth grade students throughout Indonesia.